What’s in store for females after breaking the glass ceiling? Evidence from the Chinese audit market - Cheng, Hanxiu; Wang, Jie (Frontiers in Psychology, 2023)
Given that female auditors' representation in the audit market has averagely caught up to that of males, yet remains insufficient at the partner level, it is imperative to investigate gender discrimination in public accounting firms. Using data from the Chinese audit market, this paper analyzes the glass ceiling phenomenon faced by females as they aspire to promotion to partner positions. It also explores the professional barriers that may impede their career progression post-promotion. The findings illuminate that the opportunities for female promotion to partner positions are notably lower than for males. Furthermore, after their elevation to partner roles, females are more likely to be allocated to clients grappling with financial distress and high-risk situations. In contrast, opportunities to engage with auditing important clients are diminished, particularly within male-dominated audit firms. Additionally, the study reveals that female promotion to partner positions heightens their prospects for assuming the lead auditor role in audit projects. However, this phenomenon predominantly materializes within audit firms characterized by a higher proportion of female auditors. Instead, females face more significant challenges in garnering recognition within male-dominated audit firms. Lastly, the research examines investor reactions to female promotion to partner, revealing a generally negative response. In summary, this study contributes to a comprehensive exploration of gender discrimination within the public accounting firms, shedding light on women's career development challenges after breaking the glass ceiling.